Internal audit effectiveness: Data screening and preliminary analysis - Badara, Mu'azu Saidu (Canadian Center of Science and Education, 2014)
The objective of this paper is to present internal audit effectiveness; data screening processes. Five hundred questionnaires were distributed to the respondents in various local governments in Nigeria through research assistance employed via stratified random sampling technique. Data were keyed into Statistical Package for Social Science (SPSS) version 21. Screening and cleaning of data was performed in order to suit the assumptions of multivariate analysis. Hence, response rate were ascertained, descriptive statistic, the assessment of missing data, univariate assessment and treatment of outliers, normality and multicollinearity were conducted.Similarly, Exploratory Factor Analysis (EFA) was also carried out via Principal Component Analysis (PCA).The result of the analysis revealed the significant and the suitability of the data for multivariate analysis.